Performance of Headmaster in Realizing School Climate and Entrepreneurship - Dermawati; Iim Wasliman; Hanafiah; Deti Rostini (Journal of Islamicate Studies, 2020)
The development of an education system that is built in a decentralized manner has fostered a highly competitive process. One of these developments is built on the basis of determining the principal's performance system in the entrepreneurial sphere. The focus of the Principal's Performance in Creating a School Climate and an Entrepreneurial Spirit in this study is aimed at finding an overview of the Principal's Performance in Realizing a School Climate and an Entrepreneurial Spirit. Qualitative methods are presented through the process of documentation, interviews and observations. The description describes the related scope: 1) How to plan; 2) How is the implementation; 3) How to Evaluate; 4) How about the problem; 5) How the Principal's Performance Efforts in Creating a School Climate and an Entrepreneurial Spirit. The results of research, innovation and creativity in this case are the principal's ability to create something new which is very valuable and useful for the principal himself and teachers, students and school stakeholders and is always active or creative empowered, creative, initiative and unpretentious to try in order improve the quality of schools in the activities / programs set by the school